Enhancing Self-Efficacy of Islamic Boarding School Students through Cooperative Learning via Deliberation in Islamic Religious Education - Hidayah, Nur; Imami, Agus Sulton; Agus, Abu Hasan; Hefniy, Hefniy (Seutia Hukamaa Cendekia, 2025)
This study aims to explore the implications of cooperative learning through deliberation in enhancing the self-efficacy of Islamic students. Employing a qualitative case study design, the research involved selected students and teachers purposively to provide in-depth insights. Data were collected using multiple methods, including direct observation, semi-structured interviews, and documentation, supported by observation guides, interview protocols, and official records as instruments. Data were analyzed through an interactive model comprising data reduction, data presentation, and drawing conclusions, while validity was ensured through triangulation across different sources. The findings reveal that cooperative learning through deliberation has a significant positive impact on students’ self-efficacy, as indicated by enhanced confidence in expressing ideas, greater ability to understand and explain religious materials, improved collaborative skills, and more independent learning behaviors. These results suggest that deliberation as a cooperative learning strategy fosters an interactive, supportive, and psychologically empowering learning environment, contributing to the holistic development of students’ cognitive and emotional capacities.